System component degradation: filter clogging in a UAV fuel system - Skaf, Zakwan; Eker, Ömer Faruk; Jennions, Ian K. (PHM Society, 2017)
The filtration of possible contaminant is an essential part of many engineering processes in industry. Clogging of the filtration medium is one of the primary failure modes in many application areas leading to reduced performance and efficiency. Imitation of real life clogging scenarios in laboratory conditions is not an easy task to perform, but is demonstrated here, with the profiles obtained being injected into a fuel system rig. This paper shows generic results from two benchmark rigs. One is a fuel system laboratory test-bed representing an Unmanned Aerial Vehicle (UAV) fuel system and its associated electrical power supply, control system and sensing capabilities. It is specifically designed in order to replicate a number of component degradation faults with a high degree of accuracy and repeatability. The second is a purpose built filter clogging rig designed to give quality results to aid the development of prognostic algorithms. This paper’s contribution is to show results from the filter clogging rig and derive a transfer function, the relationship between filter clogging pressures and the fuel system valve openings, to enable the fuel system rig to operate as if the clogging filter were part of the system. The results show that the local pressure drop obtained from the fuel rig can be made to closely match the pressure drop levels from the filter clogging rig. This opens up examination of the effects of filter clogging on the full fuel rig system, providing data for future system prognostic work.